Lifting the lid on Pandora’s box: Putting professional curiosity into practice - Phillips, Jake (Criminology & criminal justice, 2024)
Professional curiosity has recently become a ‘buzzword’ in the field of probation and social work. However, little research has sought to understand what professional curiosity means definitionally, conceptually or operationally. In this article, we analyse interview data from 49 probation practitioners in England and Wales to explore what professional curiosity means in the context of probation and what the main barriers are to enacting professional curiosity. We argue that professional curiosity is primarily used to assess risk and that practitioners face multiple barriers to its enactment which are rarely acknowledged or dealt with in policy and practice guides. These barriers fall into three groups: structural, relational and emotional. We conclude the article by examining the findings through the lens of neo-liberalism and probation values. The article therefore extends knowledge of professional curiosity operationally while also seeking to explain its position in a neo-liberal policy context. This research has important implications for policy and practice. Rather than simply asking practitioners to ask questions and be on the lookout for disguised compliance, probation providers should recognise and acknowledge these barriers to practice.